Brain glucose metabolism as a neuronal substrate of the abnormal behavioral response to stress in the mdx mouse, a model of Duchenne muscular dystrophy - Sébastien Goutal; Marion Lancien; François Rivier; Nicolas Tournier; Cyrille Vaillend (Neurobiology of Disease)
Duchenne muscular dystrophy (DMD) is associated with a range of cognitive and behavioral problems. Brain-related comorbidities show clinical heterogeneity depending on the position of the mutation within the multi-promoter dystrophin (DMD) gene, likely due to the differential impact of mutations on the expression of distinct brain dystrophins. A deficiency of the full-length brain dystrophin, Dp427, has been associated with enhanced stress reactivity, characterized by abnormal fear responses in both patients and mdx mouse model. However, the neural substrates of this phenotype are still unknown. Here, we undertook the first functional imaging study of the mdx mouse brain, following expression of the typical unconditioned fear response expressed by mdx mice after a short scruff restraint and one week later after recovery from stress. We compared the brain glucose metabolism in 12 brain structures of mdx and WT littermate male mice using [18F]FDG PET imaging. Restraint-stress induced a global decrease in [18F]FDG uptake in mdx mice, while no difference was found between genotypes when mice were tested one week later under non-stressful conditions. A subset of brain structures were particularly affected by stress in mdx mice, and we identified abnormal correlations between fear responses and metabolism in specific structures, and altered co-activation of the hypothalamus with several subcortical structures. Our data support the hypothesis that enhanced stress reactivity due to loss of brain Dp427 relies on abnormal activation of the brain fear circuit and deregulation of a hypothalamus-dependent pathway.